The Emergence of Surveillance Culture: The Relationships between Facebook Privacy Management, Online Government Surveillance, and Online Political Expression - Ping Yu, Rebecca (Journal of broadcasting & electronic media, 2021)
This study addresses how Facebook privacy-management openness (how comfortable Facebook users are sharing personal information) and perceived Facebook networks are interactively related to acceptance of online government surveillance and subsequent online political expression. Drawing on a nationally representative sample of Taiwanese, results indicate that while Facebook privacy-management openness is directly and positively associated with online political expression, Facebook privacy-management openness is negatively associated with online political expression indirectly through acceptance of online government surveillance. Moreover, the negative indirect relationship becomes stronger as users perceive their Facebook networks to be denser or highly connected.